2007
DOI: 10.1029/2006wr005617
|View full text |Cite
|
Sign up to set email alerts
|

Modeling multivariable hydrological series: Principal component analysis or independent component analysis?

Abstract: [1] The generation of synthetic multivariate rainfall and/or streamflow time series that accurately simulate both the spatial and temporal dependence of the original multivariate series remains a challenging problem in hydrology and frequently requires either the estimation of a large number of model parameters or significant simplifying assumptions on the model structure. As an alternative, we propose a relatively parsimonious two-step approach to generating synthetic multivariate time series at monthly or lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 24 publications
0
56
0
5
Order By: Relevance
“…Here, we used archetypal analysis (AA) to identify the spatiotemporal structure of seasonal extreme precipitation, similar to Steinschneider and Lall's [15] analysis. Unlike the principle component analysis (PCA), which is typically used for dimension reduction and analysis of the spatiotemporal variability of hydrological variables based on principle components through orthogonal transformation [16], AA represents an individual in a dataset as a convex combination of pure patterns (i.e., archetypes) or, equivalently, the extremal points. Archetypal patterns represent a set of extremal points, thus making AA widely used for extreme event analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we used archetypal analysis (AA) to identify the spatiotemporal structure of seasonal extreme precipitation, similar to Steinschneider and Lall's [15] analysis. Unlike the principle component analysis (PCA), which is typically used for dimension reduction and analysis of the spatiotemporal variability of hydrological variables based on principle components through orthogonal transformation [16], AA represents an individual in a dataset as a convex combination of pure patterns (i.e., archetypes) or, equivalently, the extremal points. Archetypal patterns represent a set of extremal points, thus making AA widely used for extreme event analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used archetypal analysis (AA) to identify the spatiotemporal structure of seasonal extreme precipitation, similar to Steinschneider and Lall's [15] analysis. Unlike the principle component analysis (PCA), which is typically used for dimension reduction and analysis of the spatiotemporal variability of hydrological variables based on principle components through orthogonal transformation [16], AA represents an individual in a dataset as a convex combination of pure Many studies have investigated the characteristics of seasonal precipitation over the basin. Gemmer et al [7] demonstrated that during the period of 1960-2004, the precipitation increased significantly in the lower Yangtze region in summer, while a statistically significant negative trend was found in September at the middle reach.…”
Section: Introductionmentioning
confidence: 99%
“…where x is aparticular time series (columns of X) E is the expectation function For our time series with a length of more than 90 months, a kurtosis greater than 0.5 indicates a non-Gaussian distribution (Westra et al, 2007). PCA is considered as a pre-processing of ICA, where the first few orthogonal components are analyzed to obtain independent components.…”
Section: Independent Component Analysismentioning
confidence: 99%
“…More recently, the higher-order statistical technique of independent component analysis (ICA, Cardoso and Souloumiac 1993;Hyvärinen 1999a, classified here as (b)) has been introduced in order to decompose these data into statistically independent components (e.g., Aires et al 2002;Westra et al 2007;Hannachi et al 2009;Frappart et al 2010Frappart et al , 2011. Forootan andKusche (2012, 2013) argue that different physical processes generate statistically independent source signals that are superimposed in geophysical time series; thus, application of ICA likely helps separating (extracting) their contribution from the total signal.…”
Section: Introductionmentioning
confidence: 99%